A cúpula mundial sobre a sociedade da informação - CSMI: foco nas políticas de informação - Lilian Emanueli Marques (2012)
The Information Society modifies the economic, political , social and cultural structures of the nations and creates the need of establishing new policies that meet these transformations. In this scenario of changes, stand out discussions related to the access to information and to the actors responsible for the task of democratizing it. It also stands out the awareness about the fact that some countries detain the control of information and communication technologies and of information itself what can, therefore, help them accumulate morepower. United Nations - UN, due to the fact that the information is not easily controlled, easilyIn this context, several countries have requested the interference of a higher organization, the exceeding national barriers, mainly because of the fast technological development. Because of the exposed reasons and because the information has being an object of study and of concern to many countries, requiring the development of public policies, both for itsmanagement, control, use, dissemination, and for the democratization of access and digital inclusion, it was considered appropriate to develop an analysis about the World Summit on the Information Society WSIS, convened by UN, organized by the International Telecommunication Union - ITU and carried out in two phases that occurred in Geneva/2003and in Tunis/2005. The objective was to understand the Summit, knowing its origin, its purposes and what its current scenario is, regarding the seven years passed since its happening and the proximity of 2015 established as the deadline for achieving the internationally agreed goals. It aimed also to investigate which type of evaluation wouldenable to measure the results after the event, from the understanding of the WSIS as a subdomain of information policies from the analysis of the database of the Summit, the WSIS Stocktakirig Platform and from the Facing the proposed objectives, it was developed a bibliographical and documentary research final documents of WSIS, through the adoption ofdigital inclusion indicators and the location of the interface between the concept of Information Literacy and the goals proposed on the WSIS Action Plan for the development of the Information Society. It was concluded that the digital inclusion indicators help in the process of understanding the goals of WSIS and its results, despite the lack of indicators that can measure the use of information and communication technologies ICT and also the phenomenon caused by this technology on society. It was also found that the development of Information Literacy is one of the goals of the WSIS, especially regarding the development ofskills to take advantage of ICTs, which expansion happens through the creation of digital inclusion programs and the development of information poiicies, athough the term is not explicit in the documents.